Moraxella Catarrhalis in Upper Respiratory Infections - Guevara Duncan, José (1997)
Otorhinolaryngologic diseases in two Hospitals of Lima, hoth in children and ill adults, were studied looking for Moraxella catarrhalis along 12 months. 318 samples front the same miniher of patients were obtained; 40% of which were negative for pathogenic bacteria. Of the remaining 60%, 31% showed Staphilococcus aurcus as the causative agent, followed by Streptococcuspneumoniae in the 19%,Miraxella catarrhalis lit 16% and Haemophilus influenzae in 10%.The most important symptom was purulent rhinorrhea.Streptococcus pneumoniae, Moraxela catarrhalis and Haemophilus influetizae were isolated, ill most of cases, front boys younger than 14 years old.15% of the S. aureus isolated strains were oxacillin-resistant, 11% of tile S. neumoniae isolated strains were penicillin- resistant, and 70% of the M. catarrhalis as well as 5% of the H. influenzae isolated strains were, lactamase producers.Our results lead us to achieve a well-oriented antimicrobial treatment to the management of tipper respiratory infections.